Influence of basalt fiber on tribological properties of secondary polyethylene terephthalate - A.-M.V. Tomina (Проблеми трибології, 2021)
The article considers the influence of discrete (3 mm) basalt fiber on the tribological properties of secondary agglomerated polyethylene terephthalate. It was found that the introduction of the filler reduces the coefficient of friction and the intensity of linear wear of the initial polymer 1,5 and 4,5 times, respectively, reaching the minimum values at a basalt fiber content of 5 mass.%. The obtained results are due to the fact that the appearance of basalt fiber strengthens the polymer matrix that confirms the increase in hardness by 15%, and inhibits the development of cracks on the surface of the composite. The study of the temperature in the contact zone showed its increase that is due to the low thermal conductivity of the filler (0,064 - 0,096); as a result, there is an accumulation of heat in the friction zone. Further increase in fiber content (up to 10 mass.%) leads to a sharp deterioration of the tribological and physico-mechanical properties of basaltoplastics because of the increase in the defect of the material. It is determined that the effective content of filler in the polymer matrix is 5 mass.%. As a result, this composite was recommended for the manufacture of parts for movable joints of agricultural, automotive and metallurgical equipment